THE EFFECT OF EDUCATIONAL VIDEO ON KNOWLEDGE AND INTEREST IN IVA TEST EXAMINATION IN WOMEN OF FERTILE AGE - Artha, Chyntia Devi; Sulistyorini, Chandra (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: Cervical cancer is one of the leading causes of death in women, which can be prevented through early detection. However, the low level of knowledge and interest of Women of Reproductive Age (WUS) towards the IVA Test examination is a challenge in prevention efforts. This study highlights the novelty of using animated video-based educational media in increasing interest in the IVA Test examination in remote areas, which has rarely been studied. Research Objective: To analyze the effect of educational videos on increasing knowledge and interest of WUS in conducting the IVA Test examination in Muara Benangaq Village, West Kutai Regency. Method: Quantitative research with a pre-experimental one group pre-test-post-test design. The sample consisted of 48 WUS selected through a purposive sampling method. Data analysis used the Wilcoxon Rank test. Results: Before the intervention, a low level of knowledge was found in 38 respondents (79%), while after the intervention it increased to 32 respondents (67%) in the good category. Initial interest in the IVA Test was low in 33 respondents (69%), and increased to 38 respondents (79%) after the intervention. Statistical analysis showed a significant increase (p-value 0.000 for knowledge, p-value 0.021 for interest). Conclusion: Animated educational videos have been proven to be effective in increasing WUS knowledge and interest in the IVA Test, especially in areas with limited access to information. The results of this study can be a recommendation for multimedia-based health education strategies to support cervical cancer prevention programs.